Unveiling the Occupational Exposure to Microbial Contamination in Conservation–Restoration Settings - Carla Viegas; Renata Cervantes; Marta Dias; Bianca Gomes; Pedro Pena; Elisabete Carolino; Magdalena Twarużek; Robert Kosicki; Ewelina Soszczyńska; Susana Viegas; Liliana Aranha Caetano; Ana Catarina Pinheiro (Microorganisms, 2022)
Assuring a proper environment for the fulfillment of professional activities is one of the Sustainable Development Goals and is contemplated in the One Health approach assumed by the World Health Organization. This particular study is applied to an often neglected sector of our society—the conservators/restorers—despite the many health issues reported by these professionals. Three different specialties (textiles, paintings and wood sculpture) and locations were selected for evaluation by placement of electrostatic dust cloths. After treatment of the samples, bacterial and fungal contamination were assessed, as well as mycotoxin determination, the presence of azole-resistant strains and cytotoxicity of the microorganisms encountered. Bacteria were only present in one of medias used and showed relatively low numbers. The highest level of contamination by fungi was identified in one of the textiles settings. The textile area also showed the highest variability for fungi. Aspergillus sp. are one indicator of possible environmental issues, and A. sections Fumigati and Circumdati were particularly relevant in two of the settings and identified in all of them. No mycotoxins were detected and the large majority of the fungi identified were non-cytotoxic. Overall, these can be considered low-contaminated environments but attention should be given to the Aspergillus sp. contamination. Additional studies are needed not only to make these results more robust, but also to test if the environmental sampling alone is the best approach in a setting where there is very little movement and dust displacement and where professionals are in very close proximity to the artefacts being treated, which may suggest the existence of a micro-atmosphere worth evaluating and comparing to the obtained results.